Multicriteria decision support model for selection of tinplate suppliers - Pinho, Rafaela Ribeiro (2022)
The evaluation and selection of suppliers has been an issue of great strategic importance over time. In this way, a structured evaluation is crucial, considering several criteria. This work reviews several multicriteria decision support methodologies explored in the literature to solve the supplier evaluation process based on CAN company specifications, strategies, and requirements. Considering the characteristics of each supplier and a set of criteria with different weights, the AHP method and the PROMETHEE method are applied to establish a ranking according to the performance in the selected criteria. In addition, to help the company make the best decision, an analysis of ranking stability is performed by varying the weights assigned to the criteria. The study and models developed were easy to apply and understand, meeting the specified objectives.